EFFECTS OF ATHLETIC TAPING ON PERFORMANCE OF BASKETBALL ATHLETES WITH CHRONIC ANKLE INSTABILITY - Gehrke,Luiza Cammerer (2018)
ABSTRACT Introduction: Ankle sprains are recurrent injuries in basketball, hence more and more athletes are taping their ankles to promote joint stability, aiming at improving dynamic balance and, consequently, functional performance. Objective: To verify the effects of elastic and rigid athletic taping on the functional performance and level of comfort of basketball players with chronic ankle instability. Methods: Twenty-one athletes aged between 18 and 30 years (mean age 23.7 ± 3.2) with chronic ankle instability (CAI), verified using the Cumberland Ankle Instability Tool, were selected to take part in this study. The Star Excursion Balance Test (SEBT) and the Figure-of-8 hop test (F8) were applied unilaterally to assess functional performance, considering the ankle of greater instability in three situations: without athletic taping, with rigid athletic taping and with elastic athletic taping. A draw was held to determine the order in which the tests (held over a number of days) would be applied. A questionnaire was conducted to assess comfort on the same day the athletic tapes were applied. Results: There was no significant difference between the tests in any direction of the SEBT, but there was a significant difference in F8 between the rigid athletic taping x control and elastic athletic taping x control situations. In addition, the elastic athletic tape was considered significantly more comfortable than the rigid athletic tape. Conclusion: Athletic taping appears to effectively improve the dynamic balance and functional performance of athletes with CAI only in activities that cause considerable joint stress, as is the case in F8. Elastic athletic tape appears to be just as effective as rigid athletic tape in these situations, in addition to being a significantly more comfortable alternative. Levef of Evidence I; High quality randomized trial with statistically significant difference or no statistically significant difference but narrow confidence intervals.